2021
DOI: 10.21787/jpb.13.2021.65-80
|View full text |Cite
|
Sign up to set email alerts
|

Indonesia’s Village Fund Program: Does It Contribute to Poverty Reduction?

Abstract: To stimulate rural development and reduce poverty in rural areas, The Government of Indonesia enacted the policy of Village Fund in 2014. However, a few studies have been conducted to examine this program. This study describes how poverty alleviation goes following Village Fund Program in Indonesia between 2015-2019. The poverty reduction was represented by holistic data, including insufficient and village status improvement through the Village Development Index (VDI). The analysis is conducted using a descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 20 publications
1
18
0
3
Order By: Relevance
“…However, village locations in Java can increase real/nominal GDRP and district economic growth. The results of this study complement the results of previous studies, such as those conducted by Saragi et al (2021), that found the increase in VDI status and the implementation of village fund allocations in 6 (six) large islands was accompanied by a decrease in poverty rates in the rural areas. Thus, the results of this study can be used as a new reference in a more detailed view of the impact of VDI status as an aggregate at the district/city level in Indonesia.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…However, village locations in Java can increase real/nominal GDRP and district economic growth. The results of this study complement the results of previous studies, such as those conducted by Saragi et al (2021), that found the increase in VDI status and the implementation of village fund allocations in 6 (six) large islands was accompanied by a decrease in poverty rates in the rural areas. Thus, the results of this study can be used as a new reference in a more detailed view of the impact of VDI status as an aggregate at the district/city level in Indonesia.…”
Section: Discussionsupporting
confidence: 87%
“…Village funds can be allocated by the village government to build small-scale infrastructure facilities and to strengthen the capacity of the local community by providing some empowerment programs (Adhayanto et al, 2019;Arifin et al, 2020). Several studies have concluded that village fund transfers can reduce poverty levels in villages (Arham & Hatu, 2020;Saragi et al, 2021;Andi Setiawan, 2019). Similar to the case in Indonesia, Thailand also has a village fund called the Thailand Village and Urban Community Fund, the results of the analysis show that the transfer of funds to the village has a positive influence on the income level of the poor in the village (Boonperm et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations